2014
DOI: 10.4172/2167-1168.1000194
|View full text |Cite
|
Sign up to set email alerts
|

How we can Enhance Nurses’ Assertiveness: A Literature Review

Abstract: Objective : Assertiveness is important for effective team building in nursing. This article aims at evaluating the results of the previous studies on nurses' assertiveness in each decade in order to discuss the possible ways for enhancing nurses' assertiveness.Methods : Five databases (PubMed, MEDLINE, CINAHL, Web of Science, and the Cochrane Library) were searched for English-language articles published from 1946 to December 2012. Article which described the assertiveness of nurses and relevant factors relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Correspondingly, the study of Wong et al (2010) revealed that authentic leadership influenced nurses' trust in their manager, which predicted voicing behavior. Review studies similarly noted that hospital administrative support and attitude of leaders or superiors were actors influencing health care professionals and nurses' speaking-up behavior for patient safety (Lee et al, 2021;Okuyama et al, 2014a). The finding of this current study indicates the valuable role of nurse leaders and managers in supporting nurses to exhibit assertive behaviors.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Correspondingly, the study of Wong et al (2010) revealed that authentic leadership influenced nurses' trust in their manager, which predicted voicing behavior. Review studies similarly noted that hospital administrative support and attitude of leaders or superiors were actors influencing health care professionals and nurses' speaking-up behavior for patient safety (Lee et al, 2021;Okuyama et al, 2014a). The finding of this current study indicates the valuable role of nurse leaders and managers in supporting nurses to exhibit assertive behaviors.…”
Section: Discussionsupporting
confidence: 56%
“…However, for most studies, these variables were correlated with general assertiveness and not specifically with workplace assertiveness of nurses. Studies have also shown that leadership, managerial, and administrative support influenced speaking-up and voicing behaviors (Darawad et al, 2020;Lee et al, 2021;Okuyama et al, 2014a;Wong et al, 2010), but the role of leader empowering behaviors on assertiveness has not been investigated. Besides, the studies earlier cited were conducted in other countries and not in the context of Filipino nurses.…”
Section: Influence Of Self-esteem Psychological Empowerment and Empowering Leader Behaviors On Assertive Behaviors Of Staff Nursesmentioning
confidence: 99%
“…However, it is still possible to evaluate the degree of symptoms intensity on a scale from perfect well-being to complete burnout [23]. Many researchers indicate that some sociodemographic data, work-related issues and the level of social competence play an important part in burnout syndrome [12,24,25], as they can both contribute to and prevent this problem [12,18,[26][27][28][29]. When performing their professional duties, physicians, nurses and paramedics face difficult, stressful situations, with which they have to deal immediately.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36] Five reviews have been written on the subject in healthcare. Three of them focused on nurses' assertiveness [37][38][39] ; one on different healthcare professionals' speaking-up behavior 40 -a form of assertiveness identified in patient safety literature-and one on quantitative studies assessing the effectiveness of assertive communication training programs for a range of health professionals and students. 41 Although some of these reviews included studies that assessed physicians as part of an entire healthcare team, they were not centred specifically on physicians.…”
Section: Introductionmentioning
confidence: 99%